Looking beyond impulse buying: A cross-cultural and multi-domain investigation of consumer impulsiveness - Sharma, Piyush; Sivakumaran, B.; Marshall, R. (2014)
Purpose: This paper aims to conceptualize consumer impulsiveness (CI) as a global trait to explore its influence on a wider range of consumer behaviours and also presents a revised CI scale. Prior research on CI focuses on the impulse buying context and does not establish the cross-cultural invariance of the CI scale. Design/methodology/approach: Two studies with undergraduate and MBA students in Singapore, UK and USA were used to develop the revised CI scale and to test its cross-cultural measurement invariance and predictive validity. Findings: CI is a three-dimensional construct with cognitive (imprudence), affective (self-indulgence) and behavioural (lack of self-control) dimensions. However, self-indulgence and lack of self-control positively (do not) correlate for consumers with independent (interdependent) self-concepts. These three dimensions also vary in their influence on different types of self-regulatory failures. Research limitations/implications: The student participants used in all the studies may be relatively younger and better educated compared to average consumers. Hence, there is a need to test the revised CI scale with diverse consumer populations. Practical implications: The revised CI scale would help future researchers study the influence of CI across diverse cultures and self-regulatory failures in a reliable and rigorous manner. Social implications: Our findings may help control the onset and spread of self-regulatory failures among young consumers by early identification of their psychological origins. Originality/value: This paper extends the scope of CI beyond impulse buying to study its impact on self-regulatory failure across five diverse behavioural domains (driving, eating, entertainment, shopping and substance abuse). © Emerald Group Publishing Limited.